Gender equality and workplace diversity in a school division office - Asher G. Cristales; Ismael A. Haguisan III; Geff B. Sagala (Jurnal Inovasi Ekonomi, 2023)
Gender equality promotes equal rights, responsibilities, and opportunities for all genders. Nowadays, organizations are adopting a globally competitive environment with programs that promote diversity, inclusion, and non-discrimination policies. This study aimed to determine the extent of the practice of gender equality and workplace diversity in a School Division Office. The respondents were 110 non-teaching employees who completed a research questionnaire. This study utilized a descriptive comparative-correlational research design. The results indicated a high extent of practice for gender equality and an even higher extent for workplace diversity. Additionally, the results revealed a significant relationship between gender equality and workplace diversity. Therefore, employees demonstrate a commitment to practicing gender equality within their diverse workplace, fostering a multicultural setting.